Polycapillary-Based X-Ray Tomography of Complex Samples with Porous Matrix; Charged and Neutral Particles Channeling Phenomena - Cherepennikov Yu. M. Yuriy Mihaylovich; Hampai D. Darjyush; Azzutti C. Claudia; Krasnykh A. A. Angelina Aleksandrovna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich; Batranin A. V. Andrey Viktorovich; Dabagov S. B. Sultan Barasbievich (2018, 2018)
Title screen